(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to develop the Volleyball Squat Max Strength (VSMS) Test instrument, as a measuring tool for leg muscle strength in volleyball athletes at the State University of Malang, by emphasizing the validity aspect. This research used the 4D Research and Development instrument development method involving 50 volleyball athletes at the State University of Malang. The validity test includes content validity, construct validity and criterion validity. The results show that the Volleyball Squat Max Strength (VSMS) Test instrument is feasible to use according to experts and has an r count of 0.82459, which is greater than r table 0.2732, so it is declared constructively valid. For the correlation test results, r count 0.7644 is greater than r table, so it is declared to have a very high correlation with the standard instrument. This instrument is much more valid for measuring leg muscle strength than the existing instrument, the leg dynamometer, because it is more specific to the characteristics of volleyball. It should be emphasized that this study did not include reliability testing or norm setting, so these findings still require further development for wider application.